The Role of Communication and Culture in the Conflict between Japan and Sea Shepherd - Gurney, Philip; Michaud, Matthew (Asian Journal of Media and Communication, 2023)
This paper delves into the intricate dynamics of the Southern Ocean conflict (2005-2017), an at times highly publicized confrontation between Japanese whaling vessels and the Sea Shepherd Conservation Society. It examines the pivotal role of cultural factors in shaping and driving this conflict. Drawing upon a range of media representations, including television, print, and digital platforms, the analysis underscores how Sea Shepherd's activities, bolstered by substantial support from a dedicated environmental activist subculture, have influenced public perception and action. Central to this study are three distinct cultural perspectives that illuminate the multifaceted nature of conflict and communication. By exploring how cultural underpinnings can both spawn and manifest within conflicts, this paper offers a nuanced understanding of the communicative expressions and cultural dimensions at play in the Japan-Sea Shepherd standoff. The findings not only shed light on this specific case but also contribute to broader discussions on the intersection of culture, communication, and environmental engagement.